Understanding influenza vaccination behaviors: a comprehensive sociocultural framework. (January 2014) - Ward, Jeremy; Raude, Jocelyn
Abstract : Despite the existence of an effective pharmaceutical means for its prevention available now for about 70 years, influenza remains an important contributor to morbidity and mortality figures due to respiratory infectious diseases through the world. Understanding why people accept or reject being vaccinated in our societies may contribute to improve substantially public health interventions in this domain by addressing the main reasons that lead individuals and groups to neglect immunization. Research into the cognitive and social causes of influenza vaccination patterns has developed over the last decades. However, it has yielded mostly inconsistent or contradictory results. To make sense of the body of data available and to improve future research, the authors argue for the adoption of a comprehensive sociocultural understanding of vaccination behavior. This could be constructed from existing social stratification models used in social sciences and should take into account how culture determines cognition.